Common mental disorders and related factors in undergraduate and graduate students from three dental schools in Cartagena, Colombia. - Miguel Simancas; Katherine Arrieta (Universidad de Concepción., 2014)
Considering the growing incidence of mental disorders in young population worldwide, the aim of this research is to estimate the prevalence of common mental disorders (CMD) and related factors in dental students from Cartagena, Colombia. Methodology: A cross sectional study will be performed on all undergraduate and graduate students of Dentistry in Cartagena, Colombia. A population of 1.072 students will be completed by taking a census. The measurement of CMD will be made through Goldberg's 12-item General Health Questionnaire (GHQ-12) using a self-administered survey about the presence of sociodemographic, personal and academic factors. It will be requested a full list of the participating dental students from each center and codes will be assigned to maintain data confiden-tiality. Once the information is collected, it will be tabulated and analyzed using descriptive and inferential statistics through X2, student's t-test and multivariate logistic regression analysis. Additionally, CMD found in the final sample will be described: anxiety and depression, social dysfunction and loss of confidence and self-esteem. The statistical analysis will be done using STATA™ for Windows. Expected outcomes: it aims to study presence and distribution of CMD among dental students and their relationship with other variables of interest. Then, taking that information into account, to suggest possible intervention strategies targeted according to risk type.